The fact of using Educational Technology and the Obstacles of Using the Educational Techniques in Basic Education Stage From Education Staff Members Attitudes - Mustafa, Naji N. (Humanities Journal of University of Zakho, 2018)
The research aims at discovering the actual using of the means and techniques of Education, which exist in the Schools for Basic Education in the govern ate center of Dohuk. And to know the major Obstacles which minimize using them. The researcher made a questionnaire to know the attitudes of the staff members concerning it. The researcher applied it on a random sample of (284) teachers at the Basic Educational Stage in the governate center of Dohuk. After showing their means and its importance of the Educational techniques in Educational process. The findings of this questionnaire are:- There is an Obvious shortage in providing Educational means and techniques in the Basic Education Schools in the governate center of Dohuk. The major Obstacles were, the crowded classrooms disallows the teacher to use these techniques, the lack of the sufficient Financial Support that may encourage inventions and school re-building, the frequent cutting out of Electricity, the lack of financial, human and technical Facilities, the lack of the necessary Educational techniques for school, the insufficiency of time for using these Educational means, the un ability to quality teachers practically to use instruments and transforming laboratories as classrooms because of the large number of students.